2018
DOI: 10.1177/0960327118814149
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic mechanisms in the 6-Hz psychomotor seizures in mice

Abstract: Serotonin (5-hydroxytrytamine (5-HT)) plays an important role in experimental seizures. Recently, we reported the depletion of 5-HT by parachlorophynylalanine (PCPA) in whole brain to enhance 6-Hz psychomotor seizures in mice. In the present work, we investigated the effect of 5-HT depletion in cortex and hippocampus, brain regions relevant for epilepsy, on behavioral and ultra-structural changes following 6-Hz psychomotor seizures in mice. In addition, we studied the effect of sodium valproate (SVP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Serotonin (S4244; Selleck, USA), 4-chloro-DL-phenylalanine (PCPA) (S4586; Selleck, USA), WAY100635 (S2663; Selleck, USA), and SB269970 (S2849; Selleck, USA) were purchased from Selleck. The concentrations of these drugs and vehicle for cannular delivery in the present study were in accordance with those described previously (27)(28)(29)(30). A c-Fos (1:3000; 2250S; Cell Signaling Technology) antibody was purchased from Cell Signaling Technology.…”
Section: Open Field Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin (S4244; Selleck, USA), 4-chloro-DL-phenylalanine (PCPA) (S4586; Selleck, USA), WAY100635 (S2663; Selleck, USA), and SB269970 (S2849; Selleck, USA) were purchased from Selleck. The concentrations of these drugs and vehicle for cannular delivery in the present study were in accordance with those described previously (27)(28)(29)(30). A c-Fos (1:3000; 2250S; Cell Signaling Technology) antibody was purchased from Cell Signaling Technology.…”
Section: Open Field Testmentioning
confidence: 99%
“…3B). Serotonin in the ACC was depleted by five consecutive pretreatments of parachlorophenylalanine (PCPA, 300 mg•kg −1 •d −1 ) as previously described (28). Next, the subjects were subdivided into PCPA and vehicle groups.…”
Section: Open Field Testmentioning
confidence: 99%
“…Moreover, it has been found that histamine content was decreased in amygdala of amygdala kindling-induced focal seizure with secondary generalized seizure (Kamei, Ishizawa, Kakinoki & Fukunaga, 1998). Besides, a reduction of brain histamine level has been found in transauricular kindling rats (Li, Liu, Zhu, Zhou & Chen, 2006), and 6-Hz stimulation mice (Jahan, Pillai & Vohora, 2017). In the audiogenic DBA/2 mice, a decrease of histamine level has been detected in the hypothalamus (Tuomisto, Sturman, Freeman & Tarhanen, 2003).…”
Section: The Change Of Central Histaminergic Signaling In Epilepsy Animal Modelsmentioning
confidence: 98%